Elementary preservice teacher preparation to teach mathematics and science in an integrated STEM framework - Kelly Overby Byrd; Sherry Herron; Rebecca Robichaux-Davis; Richard Mohn; Kyna Shelley (Journal of Research in Science, Mathematics and Technology Education, 2022)
A mixed-methods research design with a sequential, explanatory approach was used to investigate the extent to which successful completion of integrated mathematics and science methods of instruction courses related to elementary preservice teachers’ attitudes toward and confidence in teaching integrated STEM lessons. Participants (n = 24) were enrolled in their final two semesters of a teacher preparation program at a four-year public university leading to dual certification in elementary (K-6) and special education. Quantitative data were collected using the STEM Attitudes Questionnaire and the STEM Confidence Questionnaire and administered as a pre, post, and delayed post measure. Qualitative data were obtained from focus group participants and open-ended questions added to the delayed post-measures. Results indicated an overall positive change in attitudes and confidence over the 11-month period but no statistically significant difference in the participants’ attitudes toward or confidence in teaching integrated STEM lessons. Important implications for the numerous stakeholders of STEM education are presented.